Navigating The Future: Exploring The Link Between Proactive Personality and Career Adaptability Among College Students in Indonesia - Namalase, Brilliana Soroi; Gunawan, William (Jurnal Paedagogy, 2025)
This research explores the link between career adaptability and proactive personality among university students in Indonesia. Employing a quantitative correlational design, the study utilized a career adaptability scale and a proactive personality scale as instruments. A total of 1,590 students aged 18–25 years from six provinces across Java Island participated, selected through a cluster quota sampling technique. The hypothesis proposed that career adaptability would show a positive correlation with proactive personality, including its sub-dimensions. Data were examined using Spearman’s correlation analysis, resulting in a correlation coefficient of r = 0.651 (p < 0.001). This outcome demonstrates a significant positive association between career adaptability and proactive personality, thereby confirming the hypothesis. The results highlight that students with stronger proactive personality traits are more likely to exhibit higher levels of career adaptability. These findings serve as a foundation for developing targeted interventions and programs that foster proactive personality to strengthen students’ career preparedness and adaptability in response to the evolving labor market.